Nonlinear finite element analysis of equivalent Iwan model considering threaded connections - Litai Sun; Ling Li; Xiaochan Gao (Scientific Reports)
Abstract Aiming at the complex geometric nonlinearity and contact behavior of threaded connections, this study proposes a novel approach by constructing a finite element model equivalent to the Iwan model for nonlinear analysis. The innovation of this work lies in the development of a subroutine based on the Iwan model, which effectively simulates the nonlinear contact behavior inherent in threaded connections during tightening. This is followed by constructing a finite element model in Abaqus software to investigate the relationship between the applied torque and the preload force of the threads. The accuracy and nonlinearity of the model are verified against theoretical results. Furthermore, the study explores the impact of the coefficient of friction and rotational amplitude on the mechanical response of the threaded connection, providing new insights into how these factors influence preload force, stress concentration, and the risk of deformation. The results show that the finite element model based on the Iwan model can accurately capture the complex contact behavior of the threaded joint. Specifically, it is found that increasing the friction coefficient enhances the preload force but may also increase stress concentration and deformation risks. Similarly, increasing the rotational amplitude increases the preload force but may lead to plastic deformation and higher stress concentration, which has not been sufficiently addressed in previous studies.